THE EFFECT OF BAKING TIME ON PHYSICOCHEMICAL AND SENSORY CHARACTERISTICS OF CRUNCHY POTATO DONUT PRODUCTS PROCESSED FROM POTATO DONUT WASTE - Kresnayana Tri Putra; Wiwit Amrinola (Universitas Sahid, 2021)
ABSTRACT: Donuts are one of the most popular food products in the Horeka industry. One of the donut variants sold in the market is potato donuts, which is a donut made from potato tuber substitution. The weakness of this product is that it has a short shelf life, so if it is not sold it will become industrial waste. One way of handling food processing industrial waste that can still be utilized is by reprocessing it into products of economic value. This study aims to examine the effect of baking time on the physicochemical and sensory characteristics of crunchy potato donut snacks produced from potato donut industry waste. The treatments used in this study were differences in baking time, namely P1 (2 minutes), P2 (4 minutes), and P3 (6 minutes). The results showed that the baking time significantly affected the crispness, color, protein content, carbohydrate content, fat content, ash content, moisture content, and dietary fiber as well as hedonic testing which included color, aroma, taste, texture, and overall. The optimum baking time that can produce a product with good and acceptable quality is 4 minutes (P2).